Syeikh Abdul Qadir Bin Abdur Rahim Al-Fathani Bukit Bayas (1864) Towards Hadith Works and Writings of Fiqh Muamalat al-Maliyyah: An Introduction of The Malay Jawi Manuscript Entitled: Risalah fi Bayani Hukmi Bai’i war Riba - Mohd Khairul Nizam; Mahmud Ahmad; Nurul Jannah (UIN Sunan Gunung Djati Bandung, 2014)
The Malay work of writings which put Hadith as the Mawdu’ (title) of the writings of Malay Archipelago’s scholars is considered Nadir (small). This view is based on the remnants and the writings of Malay Archipelago’s scholars that are mostly focused on the aspect of tasawuf, fiqh and tauhid. This can be seen from their works or books circulated in the market that are still be read by the Malays. The historical development of knowledge in the Malay archipelago stated that the Malay ulamas have been in command of various fields of knowledge and disciplines such as Astronomy, Mathematics, Medicine and etc.This paperwork is an effort to discover the treasure of those Malay ulamas in producing written works on Fiqh Muamalat al-Maliyyahand putting hadith as a source. This writing is also to introduce Syeikh Abdul Qadir Bin Abdur Rahim Al-Fathani Bukit Bayas Terengganu and his book entitled “Risalah fi Bayani Hukmi Bai’i war Riba (papers describing on the matters of purchasing and interests). This book has been classified as a nadir (small) manuscript. This paper will also observe the method used in narrating hadith, total number of hadith and the source of hadith in the book.